Cartografia midiática de espaços fronteiriços: aproximação entre Brasil - Bolívia e Estados Unidos - México - Carvalho, Kelly Sinara Alves de (2022)
This research problematizes the performance of global media in the design of local space. We understand the confrontation of local, community spaces, as a place where media representation is present, materializing in news activity. This research questions and observes the legitimacy of international borders as spaces of danger and violence. We support the thesis that international borders correspond to spaces, not only of flow, or passage, but above all spaces for experiences, a meeting point and transculturalism between nations and that should be understood and represented in this way by the media. From a decolonial perspective, we observe border spaces through the representation made by the local media and the news produced on international borders, bringing Brazil-Bolivia and the United States-Mexico closer together in the connection regions between the states of Mato Grosso and Santa Cruz , in South America and between the states of Texas, Coahuila, Taumalipas and Nuevo León, in North America. The thesis has as general objective to study the media in the context of sociomediatic representations of Brazil-Bolivia and United States-Mexico border spaces. Its specific objectives seek to recognize theoretical contributions to the constitution of international borders and local identities on the American continent in news activity influenced by the action of global media; verify the representation of the local-international space on the Brazil-Bolivia and United States-Mexico borders; carry out a survey of the media active in the Brazil-Bolivia and United States-Mexico border areas, and analyze the news coverage that deals with them. The cartography produced shows that the Brazil-Bolivia border, in the localities of Mato Grosso (BR)-Santa Cruz (BOL), is characterized by the small population density in border municipalities and reference cities on the border; the existence of the agricultural environment with the presence of environmental reserves; the absence of twin cities; the plurality of identity groups by heredity; the cultural heritage of the Portuguese-Spanish colonial project; the Roman Catholic religious matrix as dominant and the presence of cultural marks of the Jesuit utopia in the local space; the legislation of the national border strips varying between 150 km and 50 km, respectively. On the US-Mexico border, in the place called Tex-Mex, we observe the opulence of the communication media; greater population density in border municipalities and reference cities on the border; industrial environment; presence of twin cities; historically established cultural fusion; English-Hispanic colonial project; Roman Catholic religious matrix also as dominant; presence of cultural marks of the Jesuit utopia in the local space; land demarcation disputes; legislation of national border strips 100 km. Among the results, we observed contrasting approximations between the two border spaces. The South American border space under study has a weakness in its media; the media representation takes place with the approximation of the local space and distancing from the border space. The northern hemisphere border space under study presents a vigorous media representation activity with an approximation of the local space and an approximation of the border space, which is not characterized in the global coverage. In addition, we identified a set of voices from sociocultural identities that echo across the border space, evidencing themselves from their intensities, as productivist, missionary and community voices. In the analysis of social representations based on news from local and reference media, we observe the predominance of the productivist voice that echoes with greater intensity from the media on/in the universe of international borders in the themata border with anchorage and objectification in the border as a space of violence and danger.